2008
DOI: 10.1007/978-1-59745-210-6_2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Adeno-Associated Virus Capsid in Gene Transfer

Abstract: Adeno-associated virus (AAV) is one of the most promising viral gene transfer vectors that has been shown to effect long-term gene expression and disease correction with low toxicity in animal models, and is well tolerated in human clinical trials. The surface of the AAV capsid is an essential component that is involved in cell binding, internalization, and trafficking within the targeted cell. Prior to developing a gene therapy strategy that utilizes AAV, the serotype should be carefully considered since each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
79
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 195 publications
2
79
0
Order By: Relevance
“…Gene replacement therapy with recombinant adenoassociated viral (rAAV) vectors is an attractive treatment option because of its nonpathogenic properties, specific tissue tropism of unique serotypes, and stable gene transfer caused by persistent episomal vector genomes (Van Vliet et al, 2008). Studies have demonstrated that rAAV1 vectors transduce skeletal muscle more efficiently than rAAV2 vectors, and do not elicit a humoral immune response to the transgene protein (Chao et al, 2001;Mah et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gene replacement therapy with recombinant adenoassociated viral (rAAV) vectors is an attractive treatment option because of its nonpathogenic properties, specific tissue tropism of unique serotypes, and stable gene transfer caused by persistent episomal vector genomes (Van Vliet et al, 2008). Studies have demonstrated that rAAV1 vectors transduce skeletal muscle more efficiently than rAAV2 vectors, and do not elicit a humoral immune response to the transgene protein (Chao et al, 2001;Mah et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…8,22 Among the rAAV serotypes analyzed to date, rAAV1 and rAAV8 are among the most efficient for muscle transduction. 8,[23][24][25][26] After IM administration, it was demonstrated that rAAV DNA resides as episomal circles [27][28][29] in a chromatin structure; 30 and from a biosafety perspective, the inefficient integration of rAAV into the host genome is an attractive feature for the legitimate use of this gene transfer system.…”
Section: Introductionmentioning
confidence: 99%
“…They possess the following positive attributes: they do not cause disease, have a stable virus particle that can be purified by biomedically accepted methods used for recombinant protein products, can be produced void of viral coding genes, can transduce dividing and nondividing cells, and can induce long-term transgene expression in certain cell types (10,11). The majority of gene therapy applications to date have used AAV2, including the treatment of blindness in patients with Leber's congenital amaurosis (11,12).…”
mentioning
confidence: 99%